"That Is When My Life Changed for the Better": Students' Perceptions of Exemplary School Counselors. Issue 1 (2nd January 2020) - Gallo, Laura Lynn; Bardhoshi, Gerta; Raush, Meredith
ABSTRACT: This study is an analysis of senior high school students' responses to an essay question that asked about the positive impact of their school counselors and importance in their academic, career, and personal/social development. Using thematic analysis, we analyzed 259 student college scholarship essays submitted to the School Counseling Association of a Midwestern state. The resulting six themes were personal attributes of the school counselor, professional attributes of the school counselor, process of engagement, school counseling services provided, challenging student circumstances, and personal impact of the school counselor.